In situ observation of the spatial distribution of crystalline phases during pressure-induced transformations of indented silicon thin films. Issue 3 (11th November 2014) - Gerbig, Yvonne B.; Michaels, Chris A.; Cook, Robert F.
Abstract: Abstract : Indentation-induced phase transformation processes were studied by in situ Raman imaging of the deformed contact region of silicon thin films, using a Raman spectroscopy-enhanced instrumented indentation technique (IIT). In situ Raman imaging was used to study the generation and evolution of the phase transformation of silicon while performing an IIT experiment analyzed to determine the average contact pressure and indentation strain. This is, to our knowledge, the first sequence of Raman images documenting the evolution of the strain fields and changes in the phase distributions of a material while conducting an indentation experiment. The reported in situ experiments provide insights into the transformation processes in silicon during indentation, confirming, and providing the experimental evidence for, some of the previous assumptions made on this subject. The developed Raman spectroscopy-enhanced IIT has shown its potential in advancing the understanding of deformation mechanisms and will provide a very useful tool in validating and refining contact models and related simulation studies.